Parenthood and the risk of cardiovascular diseases among 0.5 million men and women: findings from the China Kadoorie Biobank. (19th September 2016) - Peters, Sanne AE; Yang, Ling; Guo, Yu; Chen, Yiping; Bian, Zheng; Millwood, Iona Y; Wang, Shaojie; Yang, Liqiu; Hu, Yihe; Liu, Jiaqiu; Wang, Tao; Chen, Junshi; et al.
Abstract: Background: Women's parity has been associated with risk of cardiovascular disease (CVD). It is unclear, however, whether it reflects biological effects of childbearing or uncontrolled socio-economic and lifestyle factors associated with childrearing. We assessed the association between number of children and incident CVD outcomes separately in women and men. Methods: In 2004–08, the nationwide China Kadoorie Biobank recruited 0.5 million individuals aged 30–79 years from 10 diverse regions. During 7 years of follow-up, 24 432 incident cases of coronary heart disease (CHD) and 35 736 of stroke were recorded among 489 762 individuals without prior CVD. Multivariable Cox regression models were used to estimate sex-specific hazard ratios (HRs) and 95% confidence intervals (CIs) for CHD and stroke associated with number of children. Results: Overall, 98% of all participants had children and the mean number of children declined progressively from four in older participants to one or two in younger participants. Compared with childless women, women with children had an increased risk of CHD, but not of stroke [HR (95% CI): 1.14 (1.00; 1.30) and 1.03 (0.92; 1.16)]. Corresponding results for men were 1.20 (1.06; 1.35) and 1.13 (1.03; 1.24), respectively. In individuals with children, there was a log-linear association between number of children and CVD outcomes; in women, each additional child was associated with adjusted HRs of 1.02 (1.01; 1.04) for CHD and 1.02 (1.01; 1.03) for stroke, similar in magnitude to that in men [1.03 (1.01; 1.04) for CHD and 1.02 (1.01; 1.03) for stroke]. Conclusion: In Chinese adults, the association between the number of children and risk of CHD and stroke was similar between men and women, suggesting that factors associated with parenthood and childrearing are more likely to affect the risk of CVD outcomes than factors associated with childbearing.